On “Observational Instruments” composed of Stones No. 12, 13 and 14 of “Zorats Qarer” Monument - Malkhasyan, H. A.
The work is dedicated to the discussion of some of the stones of the “Zorats Qarer” megalithic monument (No. 12, 13 and 14) in terms of Astronomy. The methods of their use for observational purposes are revealed. Particularly, it has been shown that the stone No. 14 most likely served as a “seating platform” for the observer looking towards the observation angle of the stone No. 13. The other application method has been the formation of the exact direction by the principle of combining the angles of the stones No. 12 and 13. As a result of the usage of the aforementioned methods, three definite directions emerge. The examination of these directions has been performed for the possible date (9000 BC) which is crucial in terms of the origin of the ancient Armenian calendar (Protohaykian), as well as the results of the study of the monument gained so far. The results of the comprehensive examination have been combined with archeological material, Armenian ethnography and folklore. Comparisons have been drawn between days of observing the celestial bodies and important structural units of Protohaykian calendar. At the same time, the observation conditions and the mythological images of the observed stars have been discussed in the context of the most important stages of the cereal cultivation (sowing, harvesting, etc.). Parallels have been drawn with the Armenian religious beliefs (also of other nations), as well as with the results, already known from the study of this monument. The study of the mentioned stones has revealed that the stars (up to 2m.50 apparent magnitude), observable in 9000 BC, their mythological perceptions, observation conditions and days, are in complete harmony with the structure and content of the Protohaykian calendar (as well as of the ornament-calendar of the early Bronze Age vessel from Keti), and they are closely related to the worship of the Mother Goddess. Links between the observation positions and the definite stages of the cereal cultivation culture (autumn and spring sowing) reappear. There is no contradiction between previously and currently obtained results of the study of the monument. Moreover, the results obtained so far are complementary.
Keywords: Zorats Qarer; Archaeoastronomy; Ancient Observatories; Megalithic Monuments; Armenian Calendar History; Protohaykian Calendar; Cultural Astronomy; Armenian Folklore